(3CMGOjK GdeUGaMIs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s ((3eOjfI ZQfGWI s)
(3ChdgG (B:s
(3CNHQfG GdTjN Gdabjg CHh eMeO YHO GdMb Hf YHO Gdedc bO NQLfG ai TQa GdefRdI cJGHkG SejfGg HGdCMGOjK s
(3BNQgG (B:s
(3jfJgi HHGH (B( (3eG jDeQ Hg GdZRGg heG jfJghf Yfg (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(5349) s
Keywords: (3GdMOjK h GdeUWdMs